Analysis of Self Resilience Instruments on Orphaned Students at Secondary School Level in South Tambun District Using the Rasch Model - Qurrotunnisa, Zulfa; Supriatna, Mamat; Suryana, Dodi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine the validity and reliability of the self-resilience instrument for orphans in secondary school students in South Tambun District. This instrument was adapted from the resilience theory by Clarke & Nicholson (2010). The self-resilience instrument for orphans consists of 56 items covering resilience aspects, including optimism, freedom from stress and anxiety, individual accountability, openness and flexibility, and problem orientation. The study subjects were orphans, totaling 62 people across five secondary schools in the South Tambun sub-district. The Rasch model test results can be seen from the dimensionality analysis, item measure, item fit order, rating scale diagnostic, and summary. This adaptation instrument is said to be reliable by analyzing the person reliability value of 0.72 and item reliability of 0.95. The results of the data analysis show that several items need improvement and a decrease in the level of difficulty. This research helps enrich references and provide information about self-resilience in orphans.